(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: A simple spectrophotometric method for the determination of titanium is developed using 3-hydroxy-2-(2'-thienyl)-4H-chromen-4-one as a complexing agent for the metal ion in slightly alkaline solution (pH 8.0-8.5). The resulting complex bears metal to ligand ratio of 1:1 whose absorption maximum lies at 430nm. The method obeys Beer's law in the range 0.0-5.0 μg Ti ml-1 with molar absorbtivity and Sandell's sensitivity values of 1.40´104 l mol-1 cm-1and 0.0034 μg Ti cm-2 respectively. The limit of detection, of the method is 0.0086 ppm. The complex is stable for 24 hours. It is free from interference of a large number of cations and anions. Utilizing the proposed procedure, the analysis of various synthetic samples, soil, water and pharmaceutical sample has been carried out to a greater degree of accuracy.